Removal of heavy metals from textile wastewater using sugarcane bagasse activated carbon - Mohammad Razi, Mohd Adib; Al-Gheethi, Adel; Z. A, Izzatul Ashikin (Science Publishing Corporation, 2018)
Excessive release of textile wastewater with heavy metals into environment has posed a great problem to the natural water system. The efficiency of the adsorption process to remove heavy metals depend on the adsorbent. The commercial activated carbon is one of the most efficient adsorbent, but the limitation lies in the high cost. Therefore, the present study aimed to investigate the efficiency of sugarcane bagasse activated carbon modified by phosphoric acid as adsorbent for the removal of zinc (Zn) and Ferum (Fe) from the textile wastewater. The adsorption process was conducted using batch method as a function for pH (2-7), contact time (30 min to 24 h) and adsorbent dosage (0.6 to 6g). The final concentrations of the metal ions were determined by ICP-MS. The results revealed that the adsorption efficiency increased with the contact time, the optimum time was recorded after 2 h. The removal percentage of Zn and Fe associated with the adsorbent dosage due to the greater surface area with optimum value of 4.0 g. The increasing of pH from 2 to 6 correlated with high adsorption efficiency, with the optimum condition at pH 5. The maximum percentage removal of Fe, Zn was 80%. These findings indicated that the SBAC is an attractive alternative adsorbent material for the metal ions removal in textile wastewater.